Green Islamic HRM and Engagement on Employee Performance in Islamic Banks - Indira Basalamah; Muhammad Carda P (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to examine the effect of Green Islamic Human Resource Management (GIHRM) on employee performance in Islamic banks, with employee engagement serving as a mediating variable. The study is motivated by the need for Islamic banking institutions to strengthen the implementation of Islamic values, ethical governance, and environmental sustainability beyond a solely economic orientation. A quantitative approach with an explanatory research design was employed. Data were collected through structured questionnaires distributed to Islamic bank employees selected using purposive sampling. GIHRM was measured through green and Islamic recruitment, sustainability-oriented training, Islamic green performance appraisal, environmentally responsible reward systems, and workplace culture based on trustworthiness, excellence, justice, and environmental responsibility. Employee engagement was assessed through vigor, dedication, and absorption, while employee performance was measured through work quality, productivity, responsibility, Sharia compliance, service ethics, and sustainable work behavior. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that GIHRM positively affects employee engagement and employee performance. Employee engagement also positively influences performance and mediates the relationship between GIHRM and employee performance. These findings highlight the importance of integrating sustainability principles and Islamic values to enhance employee engagement and achieve sustainable organizational performance in Islamic banking institutions.